2009
DOI: 10.1093/europace/eup349
|View full text |Cite
|
Sign up to set email alerts
|

Does catheter ablation cure atrial fibrillation? Single-procedure outcome of drug-refractory atrial fibrillation ablation: a 6-year multicentre experience

Abstract: Aims In the last decade, several approaches to ablating triggers and substrates of atrial fibrillation (AF) have been developed. However, most studies have reported data only on short- or medium-term follow-up. The aim of this study was to investigate whether the 1-year efficacy of catheter ablation for AF is predictive of long-term clinical success. Methods and results Between February 2001 and October 2003, 229 consecutive patients affected by drug-refractory paroxysmal or persistent AF underwent a single ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
92
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(109 citation statements)
references
References 29 publications
12
92
1
1
Order By: Relevance
“…63,270,536,1022,1023,1024 A recent meta-analysis analyzed 19 studies including 6167 patients, describing outcomes ≥3 years after AF ablation with a mean follow-up ≥24 months after the index procedure. Single procedure and multiple procedure freedom from atrial arrhythmias has been reported to be 53% and 80%, respectively, with substantial heterogeneity noted for single-procedure outcomes.…”
Section: Early Reablationmentioning
confidence: 99%
See 1 more Smart Citation
“…63,270,536,1022,1023,1024 A recent meta-analysis analyzed 19 studies including 6167 patients, describing outcomes ≥3 years after AF ablation with a mean follow-up ≥24 months after the index procedure. Single procedure and multiple procedure freedom from atrial arrhythmias has been reported to be 53% and 80%, respectively, with substantial heterogeneity noted for single-procedure outcomes.…”
Section: Early Reablationmentioning
confidence: 99%
“…Similar findings have been reported in each of the subsequent trials. 266,267,268,1022,1086,1087 The predictors of late recurrence most commonly identified include persistent AF as well as comorbid conditions. Despite the low single-procedure, long-term success rate reported in virtually all of these clinical trials, they also reveal that with the use of repeat AF ablation procedures and/or AAD therapy, much higher rates of freedom from recurrent AF as well as concomitant reductions in AF burden can be achieved.…”
Section: Outcomes Of Af Ablation In Populations Not Well Represented mentioning
confidence: 99%
“…In the weeks after the ablation procedure, damaged endothelium represents possible nidus for thrombus formation [120,158]. Although most of AF recurrences are registered in the first 1-2 years, the attention is drawn to appearance of later arrhythmia relapse [79]. Moreover, AF recurrences after the procedure can be completely asymptomatic [3].…”
Section: Thromboembolic Complications Preprocedural Thrombosis Tranmentioning
confidence: 99%
“…whether the long-term benefits are maintained after the initial RFA procedure. Since the publication of Paper IV, a recent literature search revealed several studies on the long-term effects of the RFA treatment strategy [88][89][90][91][92], confirming the long-term efficiency of RFA. Additionally, a cost-effectiveness analysis on the firstline treatment with RFA for patients with paroxysmal AF, was found [93].…”
Section: Methodological Considerations and Discussion Of The Main Resmentioning
confidence: 93%